ANALISIS PENGARUH PENGETAHUAN, SIKAP, SARANA, DAN INFORMASI TERHADAP PERILAKU CUCI TANGAN PAKAI SABUN (CTPS) SMK KESEHATAN GANDA HUSADA TEBING TINGGI PADA ERA PANDEMI COVID-19 TAHUN 2022 - megrina, megrina; Sidabutar, Sondang; Sebayang, Amenda (Jurkessutra : Jurnal Kesehatan Surya Nusantara, 2023)
ABSTRACT                One of the way  to reduce  cases of infectious diseases is to practicing clean and healthy behaiour. Effective hand washing could reducing the risk of infectious diseases. The behavior of washing hands with soap can be influenced by many factors including knowledge, attitudes ,facilities and information obtained from various sources. The data that obtained from Ganda Husada Tebing Tinggi Health Senior High School after surveyed to ten students therewere found only 3 student (30%) who does hand washing behaviour after each activity and after finishing their activities from outside the house during the pandemic. This study aims to analyze the effect of knowledge, attitudes, facilities, and information on the behavior of washing hands with soap (CTPS) at SMK Kesehatan Ganda Husada Tebing Tinggi in the era of the COVID-19 pandemic.                    This type of study is a quantitative survey with Cross sectional study. The population of this study were all student of class X  at Ganda Husada Tebing Tinggi high school for pandemic covid-19 and The sample is 96 samples. Method of data analysis use univariate analysis, bivariate analysis and multivariate analysis with multiple logistic regression test.                  The results of the study statistically showed knowledge, attitudes ,facilities and information related to the behavior of washing hands with soap (CTP) (p 0.05). The results of multiple logistic regression test are known variables that related to the behavior of washing hands with soap are knowledge (RP = 3.99), attitude (p = 2,63), facilities (p = 2,95),  information (p = 3,35). Knowledge was the most dominant factor which influencing the behavior of washing hands with soap (CTPS)            It is suggested that it is necessary to further increase knowledge, attitudes, and information to students at school through health approaches and counseling on the importance of washing hand so as to prevent disease and students having washing hand  behavior become a daily behavior. Key words: Knowledge, Attitudes, Facilities, Washing hand